PENGARUH MASASE PUNGGUNG TERHADAP PENGURANGAN NYERI PERSALINAN: A SYSTEMATIC REVIEW - Nova Linda Rambe (Jurnal Ilmiah Kebidanan Imelda, 2021)
Pain is a physiological process. As many as 12% - 67% of women are worried about the pain that will be experienced during childbirth. One of the efforts to reduce pain is massage. is a condition in the form of a very pleasant unpleasant feeling, because the feeling of pain is different for each person in terms of scale or level. One technique to reduce pain is back massage. The theory shows that back massage is effective intermittently during labor. But at that time back massage was not done because they did not know that back massage could reduce pain. This study uses a systematic review method with the aim of seeing an effective method in overcoming labor pain. This systematic review examines articles and journals via the Google Scoolar site from 7 journals. Based on this system review, it can be guaranteed that back massage can reduce the intensity of pain in labor.